Проект Ле Морн Брабант (о. Маврикий) - Siew, Gaetan; Lampotang, Well (проект байкал, 2005)
Adopting the African village configuration, the design of each estate is revolved around the pool, which is an anchor point with the rooms on each side. Each estate is a collection of special purpose pavilions within its garden. Privacy and a sense of isolation is the design. The choice to interact with neighbours is exercised by each tenant, and is not the result of inadvertent proximity. The indoor becoming the outdoor, with the outdoor being within the Estate, is the intention; a oneness with the environment, with both the built up and the natural leading.